2022
DOI: 10.1186/s43093-022-00115-x
|View full text |Cite
|
Sign up to set email alerts
|

Earnings quality measures and stock return volatility in South Africa

Abstract: This paper examined the association between various measures of earnings quality and stock return volatility of Johannesburg Stock Exchange (JSE)-listed companies for 10 years from 2009 to 2018. The measures of earnings quality considered were accrual quality, conservatism, earnings persistence, predictability and smoothness. The stock return volatility was measured with idiosyncratic volatility. Multilevel linear regression found that accrual quality and earnings persistence are negatively related to idiosync… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Notably, regarding corporate governance, studies by Ebimobowei (2022), Marie et al (2021), andKhanifah et al (2020) documented positive significant effects, while studies by Ali et al (2020), Omesi and Appah (2021), and Boshnak (2021) reported negative effects. On the other hand, studies on financial reporting by Ayuba (2022); Aguguom et al (2019), Proença et al (2023), Ab-Hamid et al (2018), and Fonou-Dombeu et al (2022 reported mixed findings. These divergences further suggest inclusiveness and create gaps for further research.…”
Section: Empirical Reviewmentioning
confidence: 97%
“…Notably, regarding corporate governance, studies by Ebimobowei (2022), Marie et al (2021), andKhanifah et al (2020) documented positive significant effects, while studies by Ali et al (2020), Omesi and Appah (2021), and Boshnak (2021) reported negative effects. On the other hand, studies on financial reporting by Ayuba (2022); Aguguom et al (2019), Proença et al (2023), Ab-Hamid et al (2018), and Fonou-Dombeu et al (2022 reported mixed findings. These divergences further suggest inclusiveness and create gaps for further research.…”
Section: Empirical Reviewmentioning
confidence: 97%
“…As Dechow et al (2010, p. 344) mention, scholars have used numerous proxies such as "persistence, accruals, smoothness, timeliness, loss avoidance, investor responsiveness and external indicators such as restatements and SEC enforcement releases." These attributes of EQ have been rigorously studied with regard to the consequences of governance at micro and macro level (namely, as corporate governance and country-level governance) (Agnes Cheng et al, 2007;Chiang et al, 2017;Gaio and Raposo, 2014;Harymawan and Nowland, 2016;Jiang et al, 2008;Islam et al, 2022;Lobanova et al, 2019;Machuga and Teitel, 2009;Rezaee and Safarzadeh, 2023;Salehi et al, 2018;Seifzadeh et al, 2021;Thesing and Velte, 2021), International Financial Reporting Standards (IFRS) adoption (Ho et al, 2015;Houqe et al, 2012Houqe et al, , 2016Ismail et al, 2013;Kabir et al, 2010;Krishnan and Zhang, 2019;Liu and Sun, 2015;Sun et al, 2011), audit quality (Chen et al, 2018;Huang et al, 2016;Lambert et al, 2017;Lennox et al, 2016), organizational outcome (Charitou et al, 2011;Elsiddig Ahmed, 2020;Elzahaby, 2021;Fonou-Dombeu et al, 2022;Gaio and Raposo, 2011;Ma and Ma, 2017;Mensah and Onumah, 2023;Moardi et al, 2020;Nguyen et al, 2022;Saleh et al, 2020), and CSR (Bozzolan et al, 2015;…”
Section: Introductionmentioning
confidence: 99%